ChemInform Abstract: Deep Eutectic Solvents: The Organic Reaction Medium of the Century. Issue 14 (March 2016) - Alonso, Diego A.; Baeza, Alejandro; Chinchilla, Rafael; Guillena, Gabriela; Pastor, Isidro M.; Ramon, Diego J.
Abstract: Review: [140 refs.